ANALISIS PENENTUAN JUMLAH PERSEDIAAN KAS OPTIMAL DENGAN MODEL MILLER-ORR PADA PT MULTI SUKSES - Alfriyanti CH Tonapa; Ahmad Tomu (Unit Pengelola dan Pengembangan Jurnal Ilmiah dan Informasi (UPPJII) STIE Jambatan Bulan, 2019)
This study aims to determine the optimal amount of cash that PT Multi Sukses must have based on the Miller-Orr Model. Data analyzed using descriptive methods, to describe a situation or problem based on facts and data obtained and collected in this study. Data collected by observation and literature review. To answer the research problem, analysis of variance and optimal value of cash are used Mille-Orr model. The results showed the cash condition at PT Multi Sukses was classified as unfavorable, because the cash withdrawal by the owner of the company was too large which impact to the insufficient of cash availability to meet the company's short-term obligations. PT Multi Sukses's cash position in 2013 exceeded the cash limit set by the company at Rp 10,000,000.